PENCUCI MEKANIS EMPON-EMPON JAHE SISTEM SEMPROT BERTEKANAN: PERANCANGAN, P.EMBUATAN DAN PENGAPLIKASIAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Candi Garon village in Subdistric Sumowono, Semarang has a lot of herbs including ginger and turmeric that can be used as medicine, known locally as empon-empon. Empon-empon of Candi Garon is the main source of "Jamu" industry in Semarang provided their quality fulfilled the standard of the factory (i.e. the dirtiness is no more than 2%) .After harvesting, the ginger needs to be washed in order to reach the quality standard of the factory to avoid rejection or low price. In this program, we designed and manufactured an "empon-empon" washing machine to facilitate an easier, more comfortable and faster washing process by farmers. The machine is constructed from local materials in order to be easily replicated by the local farmers. The construction consists of a washing cylinder, a pump, and a transmission system. The effective capacity of the machine is 15.9kg even though it actually has a m"aximum capacity of 45 kg. It can produce 81.177%clean ginger or turmeric. The water consumption of this machine is 26.7451/min. This technology has been implemented in field trials by farmers.